(untitled) (Brazilian Journal of Health Research, 2021)
Objective: Investigating the effect of quick massage on perceived stress level and its implications in lifestyle indicators of software developers in Caxias do Sul County/RS. Methods: Interventional study based on the application of a Quick Massage software twice a week for 12 weeks. Convenience sample comprised adult male and female workers from a software development company in Caxias do Sul County, RS, to whom the intervention was applied. Each session lasted 15 minutes and was performed by a properly trained masseur, at participants’ working shift and place. In addition to the intervention, two questionnaires (Perceived Stress and Well-being Pentacle) were applied at pre- and post-intervention stages. Moreover a questionnaire was applied at pre-intervention stage in order to classify the sample (Anamnesis). Results: Twenty-seven software developers (57.7% men, at mean age 33.8±10.3 years) participated in the study. The total score of the positive well-being index corresponded to 15.4% (n=4) of the sample at pre-intervention stage, and it increased to 76.9% (n=20) of participants at post-intervention stage. Based on the total perceived stress score, there was stress index decrease from 48.1±8.2 to 34.9±5.0. Conclusion: Quick Massage is a relevant tool to help increasing workers’ quality of life indicators, as well as an important treatment against stress in this population.